2004
DOI: 10.1007/s00432-004-0600-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum-soluble interleukin-2 receptor (sIL-2R) level determines clinical outcome in patients with aggressive non-Hodgkin?s lymphoma: in combination with the International Prognostic Index

Abstract: The results suggest that a high serum sIL-2R level predicts a poor prognosis in aggressive NHL and may be a useful biomarker for selecting appropriate treatment when used in combination with the IPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 34 publications
(22 reference statements)
1
37
0
3
Order By: Relevance
“…It might not be commonly used in North America and Europe, although it has been reported that the elevated serum levels of sIL-2R have correlated with poor prognoses in a number of different types of lymphoid malignancies, particularly B-cell lymphoma, including diffuse large B-cell lymphoma and follicular lymphoma. [27][28][29][30] In Japan, it is included in the current routine practice of examinations for patients with lymphoma. The soluble form of IL-2R is naturally released by proteolytic shedding from activated T cells.…”
Section: Discussionmentioning
confidence: 99%
“…It might not be commonly used in North America and Europe, although it has been reported that the elevated serum levels of sIL-2R have correlated with poor prognoses in a number of different types of lymphoid malignancies, particularly B-cell lymphoma, including diffuse large B-cell lymphoma and follicular lymphoma. [27][28][29][30] In Japan, it is included in the current routine practice of examinations for patients with lymphoma. The soluble form of IL-2R is naturally released by proteolytic shedding from activated T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, circulating sCD25 level is considered as an indicator of the immune inhibition degree (Goto et al, 2005). Bien and Balcerska (Bien and Balcerska, 2008) suggest that in most patients with haematological malignancies, tumor cells continuously producing a large number of sCD25 is the main reason for the upregulation of sCD25.…”
Section: Discussionmentioning
confidence: 99%
“…High serum levels of the soluble form of CD25 (sCD25) have been associated with increased tumor activity, tumor aggressiveness, and also poor prognosis, mainly in human lymphoproliferative neoplasms but also in renal cell cancer and melanoma. 9,17,30 Furthermore, de novo CD25 expression was found on neoplastic lymphoid cells and to a lesser extent on nonlymphoid cancer cells such as melanoma and several carcinomas, but again, the function and impact on tumor development and behavior have not been clarified. 1,3,12,14,33,40,45 Apart from its potential role as a pro-proliferative factor, CD25 could also function as a modulator of immune-mediated tumor response.…”
Section: Discussionmentioning
confidence: 99%